2017
DOI: 10.18632/oncotarget.21962
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of CHFR methylation in non-small cell lung cancer: a systematic review and meta-analysis

Abstract: Checkpoint with Forkhead-associated and Ring finger domains (CHFR) is a G2/M checkpoint and tumor-suppressor gene. Recent publications showed the correlation of CHFR promoter methylation with clinicopathological significance of non-small cell lung cancer (NSCLC), however, the results remain inconsistent. The aim of this study is to investigate the Clinicopathological significance of CHFR promoter methylation in NSCLC with a meta-analysis. A total of nine studies were included in the meta-analysis that 816 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Indeed, the “HCC-detect” CpGs are associated with genes involved in cell cycle regulatory events, EMT transition and angiogenesis. CHFR encodes a cell cycle (G2/M) checkpoint, which was suggested to be a tumor suppressor gene 28 ; methylation of CHFR was associated with noninvasive colorectal cancer 29 , esophageal carcinoma 30 , hepatocellular carcinoma 31 , higher grade gastric cancer 32 and non-small cell lung carcinoma 33 . Vasohibin 2 (VASH2 ) gene was implicated in angiogenesis in invasive tumors 34 and was previously shown to be methylated in HCC 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the “HCC-detect” CpGs are associated with genes involved in cell cycle regulatory events, EMT transition and angiogenesis. CHFR encodes a cell cycle (G2/M) checkpoint, which was suggested to be a tumor suppressor gene 28 ; methylation of CHFR was associated with noninvasive colorectal cancer 29 , esophageal carcinoma 30 , hepatocellular carcinoma 31 , higher grade gastric cancer 32 and non-small cell lung carcinoma 33 . Vasohibin 2 (VASH2 ) gene was implicated in angiogenesis in invasive tumors 34 and was previously shown to be methylated in HCC 35 .…”
Section: Discussionmentioning
confidence: 99%
“…As a well-known negative regulator of cell cycle progression, CHFR was regarded as a tumor suppressor gene and hypermethylation in CHFR gene promoter were frequently observed in multiple cancer types, such as colorectal cancer and gastric cancer [8,11]. The methylation level of CHFR has also been proved as a biomarker for predict the prognosis in several cancers [20,21]. However, some studies also found that lower CHFR expression was independently associated with unfavorable prognosis in acute myeloid malignances [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the "HCC-detect" CGs are associated with genes involved in cell cycle regulatory events, EMT transition and angiogenesis. CHFR encodes a cell cycle (G2/M) checkpoint, which was suggested to be a tumor suppressor gene [26]; methylation of CHFR was associated with noninvasive colorectal cancer [27], esophageal carcinoma [28], hepatocellular carcinoma [29], higher grade gastric cancer [30] and non-small cell lung carcinoma [31]. Vasohibin 2 (VASH2) gene was implicated in angiogenesis in invasive tumors [32] and was previously shown to be methylated in HCC [33].…”
Section: Discussionmentioning
confidence: 99%